Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 2 - Section 2.3 - The Algebra of Functions - Exercise Set - Page 133: 60



Work Step by Step

$f(-1)=3, g(-1)=-2, f(0)=-2, g(0)=4$ $(f+g)(-1)=f(-1)+g(-1)=3+(-2)=1$ $(g-f)(0)=g(0)-f(0)=4-(-2)=4+2=6$ $(f+g)(-1)-(g-f)(0)=1-6=-5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.